Social Return on Investment Assessment of The Next Food Center under the Northeastern Regional Science Park 1, Khon Kaen Province - Sridan, Pornpod; Plainlaor, Thidasil; Yongklang, Suwanan (Journal of Health Systems Research, 2026)
This study aimed to evaluate the social return on investment (SROI) of the Next Food Center, a food innovation hub under the Northeastern Regional Science Park 1, Khon Kaen province, during 2023–2024. The assessment focused on the economic and social value generated for local food entrepreneurs, farmers, and workers. A participatory action research approach was employed, drawing on in-depth interviews, focus group discussions, and secondary data. Project outcomes were monetized using appropriate financial proxies, with adjustments for deadweight and attribution in accordance with standard SROI methodology. The results indicated that the Next Food Center project generated a total net present value (NPV) of 4,595,327 THB over the study period, using a discount rate of 3 percent. The cost–benefit analysis produced a benefit–cost ratio of 1.7, demonstrating that the project’s economic benefits exceeded its investment costs. In addition, the SROI analysis yielded a value of 0.63, indicating that for every 1 THB invested in the Next Food Center would generate 0.63 THB of verifiable social value.